Flat Stanley and the lost treasure - Houran, Lori Haskins; Brown, Jeff, 1926-2003 (I can read book., 2016)
Flat Stanley and Arthur go on a snorkeling trip and make a dazzling discovery--sunken treasure! But what happens when a storm hits and the waves get bigger and bigger?